1980
DOI: 10.1346/ccmn.1980.0280203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO2/Al2O3 Ratio on the Thermal Reactions of Allophane

Abstract: Abstract--Differences were found in the differential thermal analysis curves and in the temperatures of new-phase development between allophanes of high (1.91-1.99) and low (1.47-1.53) SiO2/A1~O3 ratios. The endothermic peak due to continuous dehydration and dehydroxylation was at higher temperatures (153 ~ 185~ for allophanes with high SiOJA1203 ratios and at lower temperatures (148~176 for those with low SiO2/A1203 ratios. The temperature of the exothermic peak was lower and the height affected more by the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…Less than 0.5% imogolite tubes could be seen by TEM. The composition and the SiOz/Al~O3 ratios (Table 1) of four samples (KIP, KyP, VA, and PA) were somewhat different from those reported previously for clay fractions from the same sources (Aomine and Wada, 1962;Yoshinaga, 1%6;Henmi and Wada, 1976;Henmi, 1980). This is presumably due to differences in sample preparation, particle size, or analytical procedure.…”
Section: Description Of Starting Materialscontrasting
confidence: 56%
See 2 more Smart Citations
“…Less than 0.5% imogolite tubes could be seen by TEM. The composition and the SiOz/Al~O3 ratios (Table 1) of four samples (KIP, KyP, VA, and PA) were somewhat different from those reported previously for clay fractions from the same sources (Aomine and Wada, 1962;Yoshinaga, 1%6;Henmi and Wada, 1976;Henmi, 1980). This is presumably due to differences in sample preparation, particle size, or analytical procedure.…”
Section: Description Of Starting Materialscontrasting
confidence: 56%
“…In Part I of this study, Henmi (1980) found significant differences in the differential thermal analysis (DTA) curves and in the temperature of new-phase development between two groups of allophanes with SiOJ A12Oz molar ratios of 1.91-1.99 and 1.47-1.53. The purpose of this paper is to examine differences in thermal stability among allophanes with different SiOJA1203 ratios by means of X-ray powder diffraction and infrared techniques.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The imogolite sample was separated from gel films which filled the in terstices of pumice beds. The detailed sample preparation methods and some mineralogical features of the samples used in this study have been published by Henmi and his co-workers (Henmi, 1977(Henmi, , 1980Henmi et al, 1981Henmi et al, , 1982Henmi et al, , 1983. Transmission electron microscopic observation showed that each of those samples is composed of "pure" allophane, imogolite or halloysite.…”
Section: Samples and Experimental Methodsmentioning
confidence: 95%
“…The samples used in this study have been characterized very carefully by some mineralogical methods such as electron microscopy, infrared absorption, X-ray diffrac tion, X-ray fluorescence and thermal analysis (Henmi, 1977;1980;1985;1986). Structural differences of allophane depending on the Si02/A12O3 ratio will be reported here.…”
Section: Introductionmentioning
confidence: 99%